2018
DOI: 10.1038/s41598-018-23437-9
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei CNCM I-3689 reduces vancomycin-resistant Enterococcus persistence and promotes Bacteroidetes resilience in the gut following antibiotic challenge

Abstract: Enterococci, in particular vancomycin-resistant enterococci (VRE), are a leading cause of hospital-acquired infections. Promoting intestinal resistance against enterococci could reduce the risk of VRE infections. We investigated the effects of two Lactobacillus strains to prevent intestinal VRE. We used an intestinal colonisation mouse model based on an antibiotic-induced microbiota dysbiosis to mimic enterococci overgrowth and VRE persistence. Each Lactobacillus spp. was administered daily to mice starting on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 79 publications
(86 reference statements)
4
23
0
Order By: Relevance
“…However, analysis of the fecal microbiome at the order level, at which we were able to assign all sequences measured, revealed that some distinct taxa were increased in relative abundance following exposure to the antibiotics. Thus, the relative abundance of Enterobacteriales reached a maximum at the end of the antibiotic treatment period in both protocol 1 and 2 and dwindled quickly thereafter, which is in keeping with the outcome of other experimental studies [47][48][49][50]. A similar Fig.…”
Section: Discussionsupporting
confidence: 89%
“…However, analysis of the fecal microbiome at the order level, at which we were able to assign all sequences measured, revealed that some distinct taxa were increased in relative abundance following exposure to the antibiotics. Thus, the relative abundance of Enterobacteriales reached a maximum at the end of the antibiotic treatment period in both protocol 1 and 2 and dwindled quickly thereafter, which is in keeping with the outcome of other experimental studies [47][48][49][50]. A similar Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The gut microbiota in patients suffering from hematological malignancies is less frequently colonized with VRE in the presence of Barnesiella (Ubeda et al, 2013). Treatment with Barnesiella or Lactobacillus paracasei CNCM I-3689 reduced VRE colonization in a mouse model (Figure 1) (Tannock et al, 2000;Crouzet et al, 2018). In clinics, one case report showed VRE decolonization after a fecal graft for the treatment of C. difficile colitis (Stripling et al, 2015).…”
Section: Probiotic Eradication Of Antibiotic Resistancementioning
confidence: 99%
“…A product containing yogurt and three probiotic candidate strains, Lactobacillus paracasei CNCM I-3689, Lactobacillus rhamnosus CNCM I-3690 and Lactobacillus paracasei CNCM I-1518, combined in a fermented milk matrix, was designed. Several preclinical studies have suggested that these three strains could modulate the gut barrier and/or the gut microbiota [15][16][17][18][19] . L. paracasei CNCM I-3689 decreased the translocation and dissemination of Listeria monocytogenes 15 , induced the clearance of vancomycin-resistant enterococci 16 and promoted the resilience of some members of the microbiota following exposure to an antibiotic challenge in mice 16 .…”
mentioning
confidence: 99%